Freedom of expression as guarantor of information - Cabrera Vélez, Juan Pablo; Ruiz Abril, Karina Marianela; Flores Pillajo, Robert Enrique (Revista Universidad de Guayaquil, 2018)
The purpose of the research entitled: "Freedom of expression as a guarantor of information". It is to know about the right to freedom of expression as one of the human being, -although pointing out that this right is erga omnes- especially in the work of journalists, who inform the State of what happened. Also, it is the purpose of this research to know the incidence that freedom of expression has on the right to information that people have, especially when this information is public, because it is of general interest. The importance of freedom of expression is that it allows to disseminate information and even opinions, which allow society to form a criterion of what happens in the environment in order to be able to make decisions that influence social life.The methodology to be used in the research is deductive, exploratory and descriptive. A qualitative approach will be used, as it is the one of the social sciences and more punctually of the Law.
Keywords: Freedom; freedom of expression; access to information; public information; constitutional guarantee